2017
DOI: 10.1093/ntr/ntx002
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Cue Reactivity: Non-Drug-Related Motivationally Relevant Stimuli Are Necessary to Understand Reactivity to Drug-Related Cues

Abstract: The cue reactivity paradigm (ie, comparing responses evoked by drug-related cues to those evoked by neutral cues) cannot provide conclusive information about the motivational relevance of drug-related cues. Responses to non-drug-related motivationally relevant stimuli should be used to appropriately gauge the level of motivational relevance that substance-dependent individuals attribute to drug-related cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 79 publications
4
46
0
Order By: Relevance
“…Preclinical studies showed that the representation of value in the brain's valuation system adapts to the range of values available at any given time (Padoa‐Schioppa, ). Hence, including a wide array of emotional categories is necessary to accurately assess the incentive salience attributed to cues predicting rewards (Oliver et al, ; Versace, Engelmann, et al, ; Versace & Schembre, ). The large LPP difference that we observed between the predictive and the nonpredictive cues in this experiment suggests that researchers interested in understanding the role of cues as triggers of compulsive eating should consider how the availability of rewards during the experiment and the presence of other emotionally arousing stimuli might impact participants' neurobehavioral responses to the cues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies showed that the representation of value in the brain's valuation system adapts to the range of values available at any given time (Padoa‐Schioppa, ). Hence, including a wide array of emotional categories is necessary to accurately assess the incentive salience attributed to cues predicting rewards (Oliver et al, ; Versace, Engelmann, et al, ; Versace & Schembre, ). The large LPP difference that we observed between the predictive and the nonpredictive cues in this experiment suggests that researchers interested in understanding the role of cues as triggers of compulsive eating should consider how the availability of rewards during the experiment and the presence of other emotionally arousing stimuli might impact participants' neurobehavioral responses to the cues.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses suggest that polymorphisms of genes influencing nAChR expression might be related to these neurophysiological profiles (Robinson et al, ). Importantly, these brain reactivity profiles are associated with differential risk of relapse: when smokers try to quit, individuals classified as C > P have significantly lower chances of achieving long‐term smoking abstinence than individuals classified as P > C (Versace et al, ; Versace, Claiborne, et al, ; Versace, Engelmann, et al, ). We interpreted these results in the light of those that emerged from preclinical studies aimed at identifying the neuropsychological underpinnings of cue‐induced compulsive behaviors (Flagel & Robinson, ; Sarter & Phillips, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time span for the included studies was from 1 January 2000 to 31 November 2018. The reference lists of the publications and related reviews [17][18][19] were also examined to identify additional studies. A study was eligible if it (i) was a task-related fMRI study, (ii) compared smokingrelated cues with neutral cues (all modalities pooled) or involved nonsmoking reward-related cues, (iii) provided peak coordinates in Montreal Neurological Institute (MNI) space or Talairach space, and (iv) measured nicotine dependence severity using the Fagerström Test for Nicotine Dependence (FTND).…”
Section: Study Selectionmentioning
confidence: 99%
“…While this provides a true non-reward baseline, it precludes the ability to determine whether the psychopathy-related reduction in cue-elicited reactivity was specific to drug-related stimuli or could instead be due to a more general reduction in reactivity to all reward-related stimuli (see Versace et al, 2017 for commentary on the pitfalls of neutral conditions). This distinction may be particularly important given that substance use disorders are known to preferentially bias neural systems toward drug-related stimuli and away from other categories of non-drug rewards (i.e., food; Baler and Volkow, 2006 ; Volkow et al, 2010 , 2016 ; Rubinstein et al, 2011 ; Schwienteck and Banks, 2015 ; Schwienteck et al, 2015 ; Versace et al, 2017 ). To this end, the present study made use of a carefully matched non-drug reward (i.e., food) condition as our control condition.…”
Section: Introductionmentioning
confidence: 99%